The prevalence of subclinical hypothyroidism in a pre-diabetes population and an analysis of related factors. (31st December 2023) - Chang, Xingyu; Wang, Yaqi; Liu, Yi; Shen, Yanyu; Feng, Jiaqing; Liu, Qianqian; Jiang, Chenjun; Yu, Jing; Tang, Xulei; Jing, Gaojing; Niu, Qianglong; Fu, Songbo
Abstract: Background: To investigate the prevalence and related influencing factors of subclinical hypothyroidism (SCH) in a pre-diabetes (PreDM) population. Patients and methods: A multi-stage stratified cluster random sampling method was used to select the adult Han population in Gansu Province for investigation. General data and related biochemical indices were recorded and SPSS software was used for statistical analyses. Results: This study selected 2876 patients, including 548 with SCH and 433 with PreDM. In the PreDM population, the levels of thyroid stimulating hormone (TSH), serum phosphorus, TPOAb and TgAb in the SCH group were higher than those in the euthyroid group ( P  < 0.05). The level of TPOAb in females of SCH group was higher than that in males ( P  < 0.05). The positive rates of TPOAb and TgAb in females were higher than those in males in the total population and SCH population. The prevalence of SCH in the PreDM group under 60 was significantly higher than that in the normal glucose tolerance (NGT) group (26.02% vs. 20.40%, χ 2  = 5.150, P  < 0.05). We defined SCH as a TSH level of >4.20 mIU/L. Using this criterion, the prevalence of SCH in the total population of PreDM was higher than that in the NGT population ( χ 2  = 8.611, P  < 0.05), the prevalence of SCH in the PreDM population generally showed an upward trend. However, we performed a separate analysis considering the accepted impact of age on TSH redefining SCH as TSH >8.86 mIU/L (for individuals over age 65). However, allowing for the expected rise in TSH levels in individuals over age 65, the prevalence of SCH in the elderly over 65 years of age decreased significantly (NGT population from 27.48% to 9.16%, PreDM population from 34.18% to 6.33%, P  < 0.05). Logistic regression analysis showed that the risk factors for SCH in the PreDM population were female gender, fasting plasma glucose and TSH (all P  < 0.05). Risk factors for SCH in the impaired fasting glucose (IFG) population were female gender, OGTT 2 h, TSH and TPOAb (all P  < 0.05). Conclusion: The prevalence of SCH in the PreDM population not considering the known physiological increase in age related TSH was relatively high and was significant in female and the IFG population. However, the effect of age on these findings needs to attract more attention. KEY MESSAGES: The prevalence of subclinical hypothyroidism (SCH) in the pre-diabetic population was analysed by cross-sectional survey. There is a great deviation in the diagnosis of SCH in the elderly with physiologically increased thyroid stimulating hormone, which needs to be redefined.